Duckweeds (Araceae: Lemnoideae) growing on wet, vertical rocks behind a waterfall in Costa Rica, with a new country record of Wolffiella oblonga (Phil.) Hegelm. - Blanco Coto, Mario Alberto (2019)
Fieldwork for this study was done during the field courses OET 2013-18 and OET 2015-18 (“Sistemática de Plantas Tropicales”) of the Organization for Tropical Studies, and during a field trip for the course “Morfología de Flores y Frutos” of the Universidad de Costa Rica.